2017
DOI: 10.1080/1343943x.2017.1398050
|View full text |Cite
|
Sign up to set email alerts
|

Variations in physiological, biochemical, and structural traits of photosynthesis and resource use efficiency in maize and teosintes (NADP-ME-type C4)

Abstract: C 4 plants show higher photosynthetic capacity and resource use efficiency than C 3 plants. However, the genetic variations of these traits and their regulatory factors in C 4 plants still remain to be resolved. We investigated physiological, biochemical, and structural traits involved in photosynthesis and photosynthetic water and nitrogen use efficiencies (PWUE and PNUE) in 22 maize lines and four teosinte lines from various regions of the world. Net photosynthetic rate (P N) ranged from 32.1 to 46.5 μmol m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
4
14
1
Order By: Relevance
“…Similar N responses of the enzymes were reported in some C 4 species such as maize (Sugiyama et al, 1984) and Amaranthus retroflexus (Sage et al, 1987). In another NADP-ME-type C 4 grass maize, Rubisco is a rate-limiting factor of photosynthesis but PEPC is not so (Usuda, 1984;Yabiku & Ueno, 2017). Therefore, it is reasonable that sorghum plants also cope with N limitation by lowering the allocation of N to PEPC more than to Rubisco.…”
Section: Anatomical Traits Of Leavessupporting
confidence: 68%
See 2 more Smart Citations
“…Similar N responses of the enzymes were reported in some C 4 species such as maize (Sugiyama et al, 1984) and Amaranthus retroflexus (Sage et al, 1987). In another NADP-ME-type C 4 grass maize, Rubisco is a rate-limiting factor of photosynthesis but PEPC is not so (Usuda, 1984;Yabiku & Ueno, 2017). Therefore, it is reasonable that sorghum plants also cope with N limitation by lowering the allocation of N to PEPC more than to Rubisco.…”
Section: Anatomical Traits Of Leavessupporting
confidence: 68%
“…stomatal density increased (Table 1). This negative relationship between the two has been found in other plants also (Franks et al, 2009;Tsutsumi et al, 2017;Yabiku & Ueno, 2017). It appears superficially that these morphological responses of stomata offset each other.…”
Section: Anatomical Traits Of Leavessupporting
confidence: 67%
See 1 more Smart Citation
“…LMA was calculated by dividing dry mass by leaf area values. The N content of dried leaf samples (0.3 g) was determined by using a micro-Kjeldahl procedure (Yabiku and Ueno 2017).…”
Section: Gas Exchange and Chlorophyll (Chl) Fluorescencementioning
confidence: 99%
“…The importance of investigating variations in leaf photosynthesis within and across species to be exploited for sustainable increases in crop yield and productivity has been emphasized (Parry et al ., 2018; Adachi et al ., 2019; van Bezouw et al ., 2019). A number of studies have shown the variation in photosynthesis and related traits within species, such as maize (Yabiku & Ueno, 2017), wheat (Driever et al ., 2014), rice (Adachi et al ., 2014; Qu et al ., 2017), soybean (Gilbert et al ., 2011), and even C 4 species Gynandropsis gynandra (Reeves et al ., 2018). Extensive comparative genetic and genomic studies have been undertaken to investigate the variation in photosynthetic efficiency across C 3 and C 4 species (Bräutigam et al ., 2011; Külahoglu et al ., 2014; Wang et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%